LOCALIZACION DE P-BRANAS EN SUPERGRAVEDAD Y TEORIA-M - Villegas Silva, Fulgencio (2006)
Recent results concerning a special class of p-brane solutions in eleven-dimensional and ten-dimensional supergravities are reviewed. Delocalised as well as localized intersections of p-branes are discussed. The new mechanism of “Blackening” localized branes is presented.